Implementing A Real Time E Learning: Why we need? - Mazlina, Abdul Majid; Noorhuzaimi@Karimah, Mohd Noor; Junaida, Sulaiman (2007)
Real time E-learning has become a new medium of educational learning. In the old days, learning is carried out in school and there is no facility for distance learning. With the emergence of e-learning, students are able to gain knowledge through online communication. However, th e process of receiving feedback from the instructors can be long and tedious. It is because any questions on their subject and assessments will take some time to be answered. Therefore, by conducting e-learning in a real time, students will able to communicate face to face with their lecturers and receive quick response to every questions arise. In a real time e-learning environment, parallel communications between instructor and students are carry out without any delay. The purpose of this paper is to highlight the advantages of real time e-learning in term of face to face interactions between instructors and students and the educational psychology (appreciation of learning). The case study discussed in this paper is based on experiences using Universiti Malaysia Pahang e-learning.